Empagliflozin for treating neutropenia and neutrophil dysfunction in 21 infants with glycogen storage disease 1b - Grünert, Sarah; Gautschi, Matthias; Baker, Joshua; Boyer, Monica; Burlina, Alberto; Casswall, Thomas; Corpeleijn, Willemijn; Çıki, Kismet; Cotter, Melanie; Crushell, Ellen; Derks, Terry G. J.; Haas, Dorothea; et al. (Molecular genetics and metabolism, 2024)
Empagliflozin has been successfully repurposed for treating neutropenia and neutrophil dysfunction in patients with glycogen storage disease type 1b (GSD 1b), however, data in infants are missing. We report on efficacy and safety of empagliflozin in infants with GSD 1b. This is an international retrospective case series on 21 GSD 1b infants treated with empagliflozin (total treatment time 20.6 years). Before starting empagliflozin (at a median age of 8.1 months with a median dose of 0.3 mg/kg/day) 12 patients had clinical signs and symptoms of neutrophil dysfunction. Six of these previously symptomatic patients had no further neutropenia/neutrophil dysfunction-associated findings on empagliflozin. Eight patients had no signs and symptoms of neutropenia/neutrophil dysfunction before start and during empagliflozin treatment. One previously asymptomatic individual with a horseshoe kidney developed a central line infection with pyelonephritis and urosepsis during empagliflozin treatment. Of the 10 patients who were treated with G-CSF before starting empagliflozin, this was stopped in four and decreased in another four. Eleven individuals were never treated with G-CSF. While in 17 patients glucose homeostasis remained stable on empagliflozin, four showed glucose homeostasis instability in the introductory phase. In 17 patients, no other side effects were reported, while genital (n = 2) or oral (n = 1) candidiasis and skin infection (n = 1) were reported in the remaining four. Empagliflozin had a good effect on neutropenia/neutrophil dysfunction-related signs and symptoms and a favourable safety profile in infants with GSD 1b and therefore qualifies for further exploration as first line treatment.
Online veröffentlicht: 27. April 2024, Artikelversion: 10. Mai 2024
Gesehen am 17.02.2025